2022
DOI: 10.1016/j.lanepe.2021.100266
|View full text |Cite
|
Sign up to set email alerts
|

Risk of candidiasis associated with interleukin-17 inhibitors: A real-world observational study of multiple independent sources

Abstract: Summary Background Biologics directed against the T-helper (Th)-17 pathway have been approved for several inflammatory diseases. Interleukin (IL)-17 is involved in anti- Candida host defense, and clinical trials suggested increased candidiasis incidence during IL-17 inhibitor therapy. We describe the worldwide epidemiology of candidiasis during Th17 inhibitor therapy, and immunological mechanisms involved in candidiasis susceptibility. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 38 publications
(42 reference statements)
3
48
0
Order By: Relevance
“…In one example of experimental vulvovaginal candidiasis (VVC), IL-17 was dispensable for protection against infection [ 23 ]. This aligns with data from humans where IL-17 deficiency does not lead to increased susceptibility to VVC [ 24 ]. Yet, others have shown that IL-17 is beneficial against Candida in the vaginal tract [ 25 ].…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…In one example of experimental vulvovaginal candidiasis (VVC), IL-17 was dispensable for protection against infection [ 23 ]. This aligns with data from humans where IL-17 deficiency does not lead to increased susceptibility to VVC [ 24 ]. Yet, others have shown that IL-17 is beneficial against Candida in the vaginal tract [ 25 ].…”
Section: Introductionsupporting
confidence: 89%
“…These findings could also be relevant to individuals receiving therapies targeting the Th17/IL-17 axis for autoimmune conditions, including psoriasis. Patients receiving these IL-17-related inhibitors have an increased risk of developing Candida infections, especially oropharyngeal and esophageal candidiasis [ 24 ]. In the HNI-induced OM model, when WT mice were administered α-IL-17A antibodies, more severe damage to the oral cavity developed [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anti-IL-17 therapy is not associated with risks to systemic candidiasis, likely because the major mechanisms of antifungal control at cutaneous/mucosal surfaces is through neutrophil recruitment and β-defensin production whereas circulating neutrophils are less IL-17-dependent (4, 41, 53, 54). In contrast, during systemic candidiasis IFN-γ, IL-12 as well as IL-17 signaling contribute to effective immunity against C. albicans (5557).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, IL-17 and Type 17 cells have been implicated in the pathogenesis of many autoimmune and inflammatory diseases (3), highlighted in the success of anti-cytokine drugs targeting IL-17 or the IL-17 receptor. Though unquestionably these drugs have improved patients' disease activity and quality of life, their use is associated with adverse side effects including worsening bowel inflammation in patients with inflammatory bowel disease (IBD) and the frequent development of opportunistic fungal infections, especially oral and espophageal candidiasis (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Biologics are associated with slightly increased risk of infections, and anti-IL17 agents are associated with an increased risk of mucocutaneous candidiasis. 171 Risks of serious infections are generally slightly higher for patients on anti-TNF than on anti-IL17 and anti-IL23 agents. 158 Increased awareness of infections and candidiasis and prescription of relevant treatment are warranted in patients on biologics and other immunomodulators.…”
Section: Treatment-related Pitfallsmentioning
confidence: 99%